2017
DOI: 10.5194/acp-17-8959-2017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating diesel engines as an atmospheric source of isocyanic acid in urban areas

Abstract: Abstract. Isocyanic acid (HNCO), an acidic gas found in tobacco smoke, urban environments, and biomass-burningaffected regions, has been linked to adverse health outcomes. Gasoline-and diesel-powered engines and biomass burning are known to emit HNCO and hypothesized to emit precursors such as amides that can photochemically react to produce HNCO in the atmosphere. Increasingly, diesel engines in developed countries like the United States are required to use selective catalytic reduction (SCR) systems to reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
1
34
2
Order By: Relevance
“…Emissions of nitrogen-containing VOCs such as HCN and HNCO are known to be highly variable depending on the type and origin of the fuel. Increasing the nitrogen content of a biogenic fuel type by 1% can increase the emission of nitrogen-containing VOCs by 2-6% (Coggon et al, 2016), and the inclusion of a diesel oxidation catalyst to a diesel engine can increase the HNCO NEMR by a factor of 30 (Jathar et al, 2017). Total isocyanate concentrations measured after burning various plastics can vary by 3 orders of magnitude Journal of Geophysical Research: Atmospheres 10.1002/2017JD027316 depending on the precursor fuel nitrogen content, and accordingly, plastics containing no nitrogen do not produce any isocyanates (Blomqvist et al, 2003).…”
Section: 1002/2017jd027316mentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions of nitrogen-containing VOCs such as HCN and HNCO are known to be highly variable depending on the type and origin of the fuel. Increasing the nitrogen content of a biogenic fuel type by 1% can increase the emission of nitrogen-containing VOCs by 2-6% (Coggon et al, 2016), and the inclusion of a diesel oxidation catalyst to a diesel engine can increase the HNCO NEMR by a factor of 30 (Jathar et al, 2017). Total isocyanate concentrations measured after burning various plastics can vary by 3 orders of magnitude Journal of Geophysical Research: Atmospheres 10.1002/2017JD027316 depending on the precursor fuel nitrogen content, and accordingly, plastics containing no nitrogen do not produce any isocyanates (Blomqvist et al, 2003).…”
Section: 1002/2017jd027316mentioning
confidence: 99%
“…The UK Environment Agency Isocyanic acid (HNCO) is another highly toxic, long-lived gas (lifetime of days to decades; Borduas et al, 2016) emitted from BB with similar anthropogenic and biogenic sources as HCN. Urban sources of HNCO are attributed to primary activity such as automotive emission (Jathar et al, 2017), residential heating (BB) (Woodward-Massey et al, 2014), and industrial processes, for example, from brick kiln emissions (Sarkar et al, 2016). A secondary source of HNCO is amide oxidation (e.g., Borduas et al, 2015), which has been observed at a suburban site in Mohali, India (Chandra & Sinha, 2016), and in an urban environment in Pasadena, California (Roberts et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2). Link et al (2016) found that diesel exhaust was a precursor for photochemical HNCO production, but Jathar et al (2017) suggested that the kinetics do not substantially outcompete dilution, and that urban HNCO is not strongly enhanced by diesel exhaust photochemistry.…”
Section: Isocyanic Acidmentioning
confidence: 99%
“…2). Link et al (2016) found that diesel exhaust was a precursor for photochemical HNCO production, but Jathar et al (2017) suggested that the kinetics do not substantially outcompete dilution, and that urban HNCO is not strongly enhanced by diesel exhaust 20 photochemistry.…”
Section: Isocyanic Acidmentioning
confidence: 99%